Addressing Students’ Difficulties in Electric Circuit Analysis Using the Modified Laboratory Problem-Solving Model - Avwiri, Eseroghene; Okey, Innocent Francis (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
The paper discussed descriptively, the resolution of students’ difficulties in electric circuit analyses, identified students’ difficulties in electric circuiting such as inability to independently conduct experiment based on direct current circuit analyses, analysis of data and making prediction using derived equation and graph. However, the model resolved these difficulties by improving teacher- student interactivity, use of specify content knowledge, students’ engaged activity, skill acquisition and engaged problem solving. Two instruments Electric Circuit Assessment Schedule (ECAS) and Modified Laboratory Problem Solving Model LAPSOM validated by two experts in Physics in the research area. They have reliability coefficients of 0.76 and 0.82 respectively Students improved on their abilities to state purpose of design (20%), experimental procedure (38%) measurement (66%) and Analysis of data (27%). The model has provided the procedural approach of identifying student’s problem, recall of procedure, predicting laws and use of mathematical analytical tools, capable of resolving students’ deficiencies in electric circuit problem solving. It suggested that modified LAPSOM model be adopted as a laboratory teaching model cum experimentation for practical knowledge in electricity circuit analyses.